(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
This scientific article is aimed at a comprehensive comparative analysis of the legal regulation related to the placement of children left without parental care in international private law. The article examines the law and practice of many national and foreign jurisdictions and explores various methods of placement, legal framework, recognition and application issues, the principle of best interests of children, mechanisms of international cooperation and emerging trends. Relying on legal sources, international conventions, case studies, and scientific literature, this article provides insight into the similarities, differences, problems, and possible areas of improvement of the legal regimes governing alternative care procedures in different countries